Biochemical and microbial food safety hazards in seafood: A Mediterranean perspective (Part 2) - Ozogul, Fatih; Rathod, Nikheel; Köse, Sevim; Alak, Gonca; Kızılyıldırım, Suna; Bilgin, Şengül; Kulawik, Piotr (Academic Press Inc., 2025)
The marine environment is teeming with a diverse array of algae, dinoflagellates and phytoplankton. These organisms possess the remarkable capacity to produce toxic compounds that can be passed to humans through the ingestion of seafood, resulting in potential health risks. Similarly, seafood can be susceptible to contamination from various microorganisms, viruses and parasites, thereby, potentially compromising food safety. Consuming seafood that contains toxins or pathogenic microorganisms may have serious health consequences, including the potential for severe illness or even fatality. This chapter delves into the various hazards that arise from biochemical and microbiological factors, with particular emphasis on the Mediterranean region. In addition, it provides a succinct analysis regarding the effect of COVID-19 pandemic on the safety of seafood. © 2025
Keywords: COVID-19; Marine toxins; Mediterranean seafood; Microorganisms; Viruses, Parasites, Food safety